A Large Segmental Mid-Diaphyseal Femoral Defect Sheep Model: Surgical Technique. Issue 6 (1st June 2022) - Margolis, David S.; Figueroa, Gerardo; Barron Villalobos, Efren; Smith, Jordan L.; Doane, Cynthia J.; Gonzales, David A.; Szivek, John A.
Abstract: Background: There are numerous animal models available to study bone healing as well as test strategies to accelerate bone formation. Sheep are commonly used for evaluation of long bone fractures due to similar dimensions and weight bearing environments compared to patients. Large critical-size defects can be created in sheep to facilitate the study of implantable materials, osteogenic proteins, and stem cell treatments. Studies have been published using plates to stabilize large critical size defects in femoral, tibial, and metatarsal defects. External fixators have also been used to stabilize tibial defects in sheep.Methods: The purpose of the current paper is to detail the surgical technique for creation of a 42 mm mid-diaphyseal femoral defect stabilization with an intramedullary device in sheep. Additional surgical details are provided for dynamization, reverse dynamization, and device removal.Conclusion: The article provides multiple technical tips applicable to this and other ovine osteotomy models and concludes with a discussion comparing the use of each stabilization technique in clinically significant large critical-size bone defects.